2005
DOI: 10.1039/b513238j
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical evidence for cyclic selenurane formation during selenomethionine oxidation

Abstract: The oxidation products of selenomethionine (SeMet) have been studied via experimental (77)Se NMR and theoretical (77)Se chemical shifts. Four signals are observed: a diastereomeric pair of selenoxides at 840 ppm and two unidentified resonances at 703 and 716 ppm. Theoretical DeltaG and chemical shifts suggest the 703 and 716 ppm resonances correspond to hypervalent selenium heterocycles, called selenuranes, formed by reaction with the amine or acid group of the amino acid and the selenoxide. To identify which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 40 publications
5
32
0
Order By: Relevance
“…These results are consistent with the assignment of the intermediate as the seleninyl sulfide A by Kice and Lee [20] who noted that selenoxides are known to strongly associate with water, but do not form the hydrate [58]. Whereas our DFT analysis [31] of the oxidation of selenomethionine showed that hydrate formation is highly endothermic (28 kcal/ mol), the DG for interconversion of A and B is much lower (<10 kcal/mol), suggesting that the intermediate may be the selenurane under certain conditions. Scheme 3.…”
Section: Interconversion Of a And Bsupporting
confidence: 94%
See 2 more Smart Citations
“…These results are consistent with the assignment of the intermediate as the seleninyl sulfide A by Kice and Lee [20] who noted that selenoxides are known to strongly associate with water, but do not form the hydrate [58]. Whereas our DFT analysis [31] of the oxidation of selenomethionine showed that hydrate formation is highly endothermic (28 kcal/ mol), the DG for interconversion of A and B is much lower (<10 kcal/mol), suggesting that the intermediate may be the selenurane under certain conditions. Scheme 3.…”
Section: Interconversion Of a And Bsupporting
confidence: 94%
“…In terms of the pH-dependence observed by Kice and Lee [20], these observations may suggest that path A1 or the seleninyl sulfide product is favored under basic conditions whereas the selenurane intermediate is preferred under acidic conditions. This conclusion is consistent with the occurrence of a selenurane in equilibrium with the selenoxide of SeMet, observed experimentally by our research group [31].…”
Section: Reaction Steps A1 and B1supporting
confidence: 92%
See 1 more Smart Citation
“…[28-30] The selenium analog of methionine ( 4 , X = Se) is also easily oxidized with biological oxidants such as hydrogen peroxide to give a mixture of selenoxide 7 (X = Se) and hydrate in the neutral pH range. [28,31,32] NMR data is pH dependent, and only single compounds are seen at low pH[28,33] and at high pH. [28,32] These data are consistent with studies of other selenoxides.…”
Section: Introductionsupporting
confidence: 77%
“…They identified the intermediate as either a seleninyl sulfide (A) or a hypervalent selenurane (B) resulting from reaction of the first equivalent of thiol with seleninic acid (Scheme 4). Selenuranes such as B have been proposed as intermediates in ROS scavenging by several organoselenium compounds (79)(80)(81). The second step consisted of the conversion of the intermediate to the selenenic acid, which is rapidly converted to the selenenyl sulfide.…”
Section: Phseo 2 Hmentioning
confidence: 99%